Maternal uniparental disomy of chromosome 16 [upd(16)mat]: clinical features are rather caused by (hidden) trisomy 16 mosaicism than by upd(16)mat itself. Issue 1 (8th March 2017) - Scheuvens, R.; Begemann, M.; Soellner, L.; Meschede, D.; Raabe‐Meyer, G.; Elbracht, M.; Schubert, R.; Eggermann, T.
Abstract : Maternal uniparental disomy of chromosome 16 [upd(16)mat] as the result of trisomy 16 is one of the most frequently reported uniparental disomies in humans, but a consistent phenotype is not obvious. Particularly, it is difficult to discriminate between features resulting from upd(16)mat and mosaic trisomy 16. By evaluating literature data ( n  = 74) and three own cases we aimed to determine whether the clinical features are due to upd(16)mat or to trisomy 16 mosaicism. While in single cases the clinical symptoms were caused by homozygosity of autosomal recessive mutations on chromosome 16, it turned out that clinical features in upd(16)mat are caused by (hidden) trisomy 16 mosaicism and a specific chromosome 16‐associated imprinting disorder does not exist. In trisomy 16/upd(16)mat pregnancies, the management should be based on the ultrasound results and on the clinical course of the pregnancy. In fact, mosaic trisomy 16 pregnancies require a close monitoring because of the higher risk for hypertensive disorders. Postnatal testing for upd(16)mat should be considered in case of homozygosity for an autosomal‐recessive mutation, in individuals carrying chromosome 16 aberrations and in phenotypes comprising features of the trisomy 16/upd(16)mat spectrum. Finally, upd(16)mat probably represents a bioindicator for a hidden trisomy 16 mosaicism. Abstract :